2017
DOI: 10.1021/acsami.7b02199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Oxygen Electrode Open Ratio and Electrolyte Evaporation on the Performance of Li–O2 Batteries

Abstract: This study experimentally investigates and numerically simulates the influence of the cathode electrode open ratio (ratio of oxygen-opening area to the total electrode surface area) on the performance of Li-O batteries at various discharge current densities. At the current density of 0.1 mA/cm, the maximum discharge capacity is achieved at 25% open ratio among the tested open ratios (0-100%). As the open ratio increases from 25% to 100%, the specific discharge capacity decreases from 995 to 397 mA h/g. A simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Figure b shows the EIS curves of the two batteries after discharge at high and medium frequency. The curves exhibit a high frequency depressed semicircle roughly between 50 kHz and 1 kHz, and a medium frequency depressed semicircle in the region of 1 kHz and 2 Hz, which is caused by the dispersion of two different processes . The first semicircle corresponds to the electrolyte bulk resistance and electronic resistance of the current collector, and the second one relates to the parallel combination of the charge-transfer resistance or kinetic resistance relates to slow lithium ion transfer coupled with the double layer capacitance of cathodes .…”
Section: Resultsmentioning
confidence: 99%
“…Figure b shows the EIS curves of the two batteries after discharge at high and medium frequency. The curves exhibit a high frequency depressed semicircle roughly between 50 kHz and 1 kHz, and a medium frequency depressed semicircle in the region of 1 kHz and 2 Hz, which is caused by the dispersion of two different processes . The first semicircle corresponds to the electrolyte bulk resistance and electronic resistance of the current collector, and the second one relates to the parallel combination of the charge-transfer resistance or kinetic resistance relates to slow lithium ion transfer coupled with the double layer capacitance of cathodes .…”
Section: Resultsmentioning
confidence: 99%
“…It was claimed from another simulation study that the evaporation of the electrolyte is proportional to the oxygen flow rate passing through the battery as well as proportional to the exposed surface area of the oxygen electrode. [ 96 ] The loss of electrolyte stops the electrochemical reaction in the dry pores in the cathode because of the lack of a three‐phase boundary (which requires O 2 , electrolyte, and carbon). In general, electrolytes with higher boiling points are preferred because of their low evaporation rates.…”
Section: Challenges On the Way Toward Ambient Air Operationmentioning
confidence: 99%
“…Adversely, it was independent of Li + concentration when the concentration was above 0.1 M. Kwon et al 139 revealed that 0.5−0.7 atm of O 2 partial pressure could result in the highest discharge capacity. Mohazabrad et al 141 devoted their time to studying the electrolyte evaporation. They found that O 2 diffuser, which is a titanium chip with holes, inserted with the cathode could more uniformly distribute the O 2 flow.…”
Section: Porous Cathode Electrodementioning
confidence: 99%